Komparasi Model Pembelajaran Project-Based Learning Dengan Experiental Learning Pada Pembelajaran Kewirausahaan SMK - Riza, Fahru; Chisbiyah, Lismi Animasi (Universitas Nahdlatul Ulama Blitar, 2024)
This research examines and compares the effectiveness of Project-Based Learning (PBL) and Experiential Learning (EL) learning models in the context of entrepreneurship education at Vocational High Schools (SMK). This research method uses a descriptive qualitative approach. This type of research is a literature review with the PICOC data collection technique. The results of this research are PBL, which focuses on real solutions to problems, increases students' creativity, communication and collaboration abilities, and is effective in increasing interest and learning outcomes. Meanwhile, EL provides hands-on experiences that enable students to actively build entrepreneurial knowledge and skills, with learning modules and gamification elements that enrich the learning experience. Both have proven success in forming character, improving entrepreneurial skills, and developing students' soft skills. These findings are supported by the latest literature from accredited national and international journals. This research confirms that PBL and EL provide a significant positive contribution in supporting the development of vocational school students to be successful in the world of entrepreneurship, with important implications for curriculum design and learning strategies at the vocational secondary education level.